2009
DOI: 10.3892/ijmm_00000273
|View full text |Cite
|
Sign up to set email alerts
|

Activation of peroxisome proliferator-activated receptor-γ induces apoptosis on acute promyelocytic leukemia cells via downregulation of XIAP

Abstract: Abstract. In the present study we investigated the in vitro apoptosis inducing effects of peroxisome proliferator-activated receptor-Á (PPAR-Á) ligand ciglitazone (CGZ) on acute promyelocytic leukemia (APL) NB4 cells and its mechanisms of action. The results revealed that CGZ (10-50 μmol/l) inhibited the growth of leukemia NB4 cells and caused apoptosis in a time-and dose-dependent manner. Apoptosis was observed clearly by flow cytometry (FCM) and DNA fragmentation analysis. After treatment by CGZ for 48 h, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…PPAR␥ is a ligand-activated transcription factor, a member of the nuclear hormone receptor (NHR) superfamily expressed in many tissues (Meng et al, 2010), it is a potent cell proliferation inhibitor through induction of cdk inhibitors, its expression was increased concomitantly when apoptosis occurred, treatment of cancer cells with PPAR␥ ligands led to growth inhibition and apoptosis of cancer cells (Liu et al, 2009;Meng et al, 2010). Cell cycle progression is accelerated by cyclins and decelerated by cyclin-dependent kinase (CDK) inhibitors, such as cyclin D1 and Rb, transition through G 1 into S phase requires the activation of cyclin D and cyclin E (Hu et al, 2002;Yoshida et al, 2010;Sun et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…PPAR␥ is a ligand-activated transcription factor, a member of the nuclear hormone receptor (NHR) superfamily expressed in many tissues (Meng et al, 2010), it is a potent cell proliferation inhibitor through induction of cdk inhibitors, its expression was increased concomitantly when apoptosis occurred, treatment of cancer cells with PPAR␥ ligands led to growth inhibition and apoptosis of cancer cells (Liu et al, 2009;Meng et al, 2010). Cell cycle progression is accelerated by cyclins and decelerated by cyclin-dependent kinase (CDK) inhibitors, such as cyclin D1 and Rb, transition through G 1 into S phase requires the activation of cyclin D and cyclin E (Hu et al, 2002;Yoshida et al, 2010;Sun et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Conjugated linoleic acid is established as a PPARc ligand; it can modulate cellular proliferation and differentiation through the activation of peroxisome proliferatoractivated receptors (PPARs), and showed an anticancer effect on some human cancer cells [7,30]. CLA inhibited human breast cancer cell proliferation through stimulating the expression of PPARc to levels up to control; PPARc expression was increased concomitantly when apoptosis occurred [31], but the other apoptosis-related gene expressions varied to some degree. Previous investigations showed that trans-10, cis-12 (t10, c12) CLA inhibited the proliferation of human prostatic carcinoma cells, decreased bcl-2 gene expression, and increased p21 (WAF1/Cip1) mRNA levels [32]; t10, c12 CLA induced colon cancer cell apoptosis, and increased the levels of cleaved caspase-9 and caspase-3, but did not alter the levels of Bcl-2 family member proteins [33].…”
Section: Discussionmentioning
confidence: 98%
“…PPARγ , a member of the NHR superfamily expressed in many tissues, is a ligandactivated transcription factor (43) and a potent cell proliferation inhibitor through induction of cdk inhibitors, its expression was increased concomitantly when apoptosis occurred, cancer cells treated with PPARγ ligands led to growth inhibition and apoptosis of cancer cells (42)(43)(44). Further, the Bcl-2 family proteins, including proapoptotic members such as Bax, Bak, and antiapoptotic members such as Bcl-2 and Bcl-xL, play an important role in the regulation of mitochondrial-mediated apoptosis Downloaded by [George Washington University] at 23:11 08 February 2015 FIG.…”
Section: Discussionmentioning
confidence: 99%